Question Bank - 100 Algebra Questions From Previous CAT Papers (Solved)



  • Solution: First part of the question :
    f(3) = 0. So 9a + 3b + c = 0
    f(5) = -3f(2). So 25a + 5b + c = -3 (4a + 2b + c). Solving, we get 37a + 121b + 4c = 0.
    So we have 2 equations:
    9a + 3b + c = 0 ---> (1)
    37a + 11b + 4c = 0 ---> (2)
    Multiply (1) with 4 , we get, 36a + 12b + 4c = 0 ---> (3)
    Subtract (3) from (2), we get, a – b = 0 or a = b. So, we got a = b.
    Sum of the roots of a quadratic equation is –b/a. Here it is –a/a = -1
    one of the root is 3. Sum of roots is -1. Hence the other root is -4.

    Second part :
    We know the roots are 3 and -4.
    Hence the equation is (x-3) (x+4) = 0, or x^2 + x – 12 = 0.
    However, even 2(x^2 + x – 12) = 0 or 100 (x^2 + x – 12) = 0 and so on will have the same roots.
    Hence, we cannot find unique values of a,b,c.



  • Q8) Let f(x) = ax^2 – b |x| , where a and b are constants. Then at x = 0, f(x) is:
    a. maximized whenever a > 0, b > 0
    b. maximized whenever a > 0, b < 0
    c. minimized whenever a > 0, b > 0
    d. minimized whenever a > 0, b < 0



  • Method 1 :
    f(x) = ax^2 – b|x|
    x^2 and |x| are always non negative.
    If a > 0 and b < 0, f(x) > = 0
    So at x = 0, f(x) is minimum when a > 0 and b < 0
    Option d.

    Method 2 :
    f(x) = ax^2 – b|x|
    To find max and minimum value, we have to double differentiate.
    First differential f ' (x) = 2ax – b * ( |x|/x ). At x = 0, f ' (x) = -b.
    Second differential f '' (x) = 2a.
    If a > 0, then f '' (x) is positive and hence the equation is minimal.
    Also for the minimal value at x = 0, b is less than 0.



  • Q9) If f (x) = x^3 – 4x + p, and f (0) and f (1) are of opposite signs, then which of the following is necessarily true?
    a. –1 < p < 2
    b. 0 < p < 3
    c. –2 < p < 1
    d. –3 < p < 0



  • f(0) = p
    f (1) = 1 – 4 + p = p + 3.
    p and p+3 are of different signs.
    Substitute for the options:
    1st option, if p is a negative number, then p – 3 is also negative, and both are same sign.
    For 3rd and 4th option, also it is the same.
    For the 2nd option, value of p is between 0 and 3, and p – 3 is negative. Hence it agrees.
    Even without substituting the answer can be found out. As p and p – 3 are different signs; p should be between 0 and 3.



  • Q10)
    0_1514381317372_cfe92056-4036-4a4b-ab4f-29bb44144827-image.png



  • Solution: 1st sub question:
    We need to multiply g with g till we reach e as the solution
    g^2 = g * g = h
    g^3 = g * g * g = h * g =f
    g^4 = h * g * g = h * h = e
    So g^4 = e.

    2nd sub question:
    Solve from the innermost bracket.
    f * f = h
    f ⊕ h = e
    f * e = f
    f + f = h

    3rd sub question:
    g^9 = g^2 * g^2 * g^2 * g^2 * g = h * h * h * h * g = e * e * g = e * g = g
    f ^10 = f^2 * f^2 * f^2 * f^2 * f^2 = h * h * h * h * h = e * e * h = e * h = h
    a^10 = a^2 * a^2 * a^2 * a^2 * a^2 = a * a * a * a * a = a * a * a = a * a = a
    e^8 = e^2 * e^2 * e^2 * e^2 = e * e * e * e = e * e = e
    So, the equation reduces to [a * (h ⊕g)] + e = [a * f ] + e = a + e = e



  • Q11. (CAT 2002)
    If u, v, w and m are natural numbers such that u^m + v^m = w^m, then which of the following is true?
    (1) m < Min (u, v, w)
    (2) m > Max (u, v, w)
    (3) m < Max (u, v, w)
    (4) None of these



  • The question does not specify that u, v, m and w are distinct. The best way to go about this is by trial and error method.
    Let us have m = 1. If u = 1, v = 1, then w = 2.
    We get the 1st 2 options wrong hence. So, we can either have 3rd option or 4th option right here.
    Now, let us have m = 2. If m = 2, we have the equation as u^2 + v^2 = w^2
    This is basically a Pythagorean triplet. Examples are u = 3, v =4, w = 5 or u = 5, v = 12, w = 13 etc etc. Hence here also, we see that m < Max (u, v, w). If we put m = 3, we see that the lowest of the two numbers cannot be any combination of 2, 3, 4. i.e.

    (u, v) cannot be (2,2) as w will not be natural number.
    (u, v) cannot be (2,3) as w will not be natural number.
    (u, v) cannot be (2,4) as w will not be natural number.
    (u, v) cannot be (3,3) as w will not be natural number.
    (u, v) cannot be (3,4) as w will not be natural number.
    Hence m will be lesser than u, v and w for sure.

    Hence the answer would be m < Max (u, v, w).

    However, if it is mentioned that u, v, w and m are distinct, then the most suited will be Pythagorean triplets or the next case discussed. i.e. We will not have the 1st case where m = 1 and u = 1. u has to be minimum 2 then (distinct). Hence, m is always less than min (u, v, w). (If distinct is mentioned in the question). So, basically,

    If the numbers are distinct, then m < Min (u, v, w)
    If the numbers are not distinct, then m < Max (u, v, w)



  • Q12. (CAT 2006)
    If logy(x) = a * logz(y) = b * logx(z) = a * b, then which of the following pairs of values for (a, b) is not possible?
    (1) -2, 1/2
    (2) 1, 1
    (3) 0.4, 2.5
    (4) π, 1/π
    (5) 2, 2



  • Solution: A little understanding on the theoretical side of logarithms is necessary for solving such questions. If you do not have much theoretical understanding of log, you should know the following at least :

    log_10(100) = 2 (You have to know this)
    log_10(1000) = 3 (It is easy to remember such things, compared to the formulas)
    This means, 10^2 = 100, 10^3 = 1000. That means log_x(y) = a means x^a = y.

    Also you need to know, log_x(y) = log y/log x (Both to the same base, 10 or e or anything)
    Now, moving on to the question,
    We know, a * log_z (y) = a * b. So, log_z (y) = b.
    We know, b * log_x (z) = a * b. So, log_x (z) = a.
    We know, log_y (x) = a * b
    Substituting equations 1 and 2 in equation 3, we get,
    log_y (x) = log_z(y) * log_x (z)
    log x/log y = log y/log z * log z/log x
    log x/ log y = log y / log x
    log x^2 = log y^2
    log x = log y or log x = - log y
    x = y or x = 1/y
    We know that log y x = a * b
    So a * b = log y y or log y 1/y (Substituting for x = 1/y, in the above equation)
    So a * b = 1 or a * b = -1.
    See from the options, which value of (a, b) does not obey the above.



  • Q13. (CAT 2008)
    If the roots of the equation x^3 – ax2 + bx – c =0 are three consecutive integers, then what is the smallest possible value of b ?
    (1) -1/√3
    (2) -1
    (3) 0
    (4) 1
    (5) 1/√3



  • Solution: For an equation with power 3, the co-efficient of x is the sum of the individual product of the roots.
    Let (n-1), n, (n+1) be the roots of the equation. So, n(n-1) + n(n+1) + (n-1)(n+1) = b
    n^2 – n + n^2 + n + n^2 – 1 = b
    3n^2 – 1 = b.
    We know that n^2 is positive, the minimum value of n^2 will be 0 when n = 0. So, the minimum value of b is -1 when n = 0.



  • Q14. (CAT 2005)
    For which value of k does the following pair of equations yield a unique solution for x such that the solution is positive?
    x^2 – y^2 = 0
    (x – k)^2 + y^2 = 1
    (1) 2
    (2) 0
    (3) √2
    (4) -√2



  • Solution: From 1st equation x^2 = y^2.
    Substituting for y^2 in the 2nd equation, we get, (x – k)^2 + x^2 = 1
    x^2 + k^2 – 2kx + x^2 = 1
    2x^2 - 2kx + (k^2 – 1) = 0
    For unique solution, Discriminant D should be 0. (D = b^2 – 4ac)
    D = 4k^2 – 8 (k^2 – 1) = 8 – 4k^2
    So, for unique solution, 8 – 4k^2 is 0
    4k^2 = 8 => k^2 = 2 => k = √2 or -√2
    We require the positive solution, substituting, we get positive solution for k = √2



  • Q15. (CAT 2005)
    If x ≥ y and y > 1, then the value of the expression logx(x/y) + logy(y/x) can never be
    (1) -1
    (2) -0.5
    (3) 0
    (4) 1



  • Solution: Let us take everything to the same base, so that it is easier.
    log_x(x/y) = (log x – log y)/ log x
    log_y(y/x) = (log y – log x)/ log y
    Adding these 2, we have (log x – log y)/ log x + (log y – log x)/ log y,
    1 – (log_y/log x) + 1 – (log x/ log y)
    2 - (logy/log x) - (log x/ log y)
    2 – (log_x y + log_y x) (As, log y/log x = log_x y and log x/ log y = logy x)
    Now, we know y > 1 and x ≥ y. So, log_x y < 1, and logy x > 1 (You can try out by taking examples as x = 100 and y = 10 or similar).
    So, we have the expression 2 - (log x y + log y x) as 2 – (a number greater than 1).
    So, our result is lesser than 1 always.



  • Q16. (CAT 2004)
    f1 (x) = x when 0 ≤ x ≤ 1
    = 1 when x ≥ 1
    = 0 otherwise
    f2 (x) = f1(–x) for all x
    f3 (x) = –f2(x) for all x
    f4 (x) = f3(–x) for all x

    How many of the following products are necessarily zero for every x:
    f1(x) f2 (x)
    f2 (x) f3 (x)
    f2(x) f4 (x)
    a. 0
    b. 1
    c. 2
    d. 3

    Which of the following is necessarily true?
    a. f4(x) = f1(x) for all x
    b. f1(x) = –f3(–x) for all x
    c. f2(–x) = f4(x) for all x
    d. f1(x) + f3(x) = 0 for all x



  • Solution: We have to consider positive and negative numbers for all the cases.
    f1(x) is positive for positive numbers, and 0 for negative numbers. (0 for x = 0)
    f2(x) is 0 for positive numbers, and positive for negative numbers. (0 for x = 0)
    f3(x) is 0 for positive numbers, and negative for negative numbers. (0 for x = 0)
    f4(x) is negative for positive numbers, and 0 for negative numbers. (0 for x = 0)
    So, we see that, out of the 3 products in the question, f1(x) * f2(x) and f2(x) * f4(x) are always zero, for any x.

    Second sub question, f4(x) = f3(-x) = -f2(-x) = -f1(x).
    Hence, 1st option is false.
    –f3(-x) = f2(-x) = f1(x). Hence this is true.



  • Q17. (CAT 2003)
    If 1/3 log_3M + 3 log_3N = 1 + log_0.0008 (5), then:
    (1) M^9 = N/9
    (2) N^9 = 9/M
    (3) M^3 = 3/N
    (4) N^9 = 3/M


Log in to reply